Loomis, Ch. y Loomis, Z. K. (ed.), Socio-Economic Change and the Religious Factor in India. An Indian Symposium of Views on Max Weber, Affiliated East-West Press, Pvt. Ltd., New Delhi y Van Nostrand Reinhold Company, Nueva York, Londres, Melbourne, Toronto (1969). - G. S., S. (Estudios de Asia y África, 1971)
-